Isolation and Characterization of Bacteria with Biochemical and Pharmacological Importance from Soil Samples of Dhaka City - Begum, Kohinur; Mannan, Sultana Juhara; Rezwan, Refaya; Rahman, Md Mahinur; Rahman, Md Shajidur; Kamal, Alam Nur E (Dhaka University Journal of Pharmaceutical Sciences, 2017)
We studied soil samples from Dhaka municipality area to isolate and characterize bacteria having potential biochemical and pharmacological importance. Total twenty five soil samples were collected from fish, vegetables and fruits dump area from Dhaka City. Bacterial population was sub-cultured in trypticase soya agar (TSA) plate. Nineteen colonies were isolated, cultured and characterized by gram staining and biochemical tests. Six isolates were found to be gram negative while thirteen were gram positive. All isolates were positive in oxidase, catalase, citrate, and protease tests. Eight isolates showed coagulase negative and nine were coagulase positive. It was found that all bacterial isolates were sensitive to tetracycline, chloramphenicol, gentamycin, ciprofloxacin, azithromycin and ceftriaxone. About 95% of the bacterial isolates were resistant to penicillin-G and ampicillin. About 89%, 26%, 21% and 11% of the bacterial isolates were resistant to amoxicillin, co-trimoxazole, nalidixic acid and erythromycin, respectively. It was found that bacterial isolates produce chemical(s) inhibitory to other bacterial strains including both gram positive and gram negative bacteria. Further studies are needed to characterize the potential antibacterial factor(s) and other bioactive compound (s) present in these bacterial isolates from soil samples. Dhaka Univ. J. Pharm. Sci. 16(1): 129-136, 2017 (June)